2018
DOI: 10.1097/hjh.0000000000001820
|View full text |Cite
|
Sign up to set email alerts
|

Distinct factors are related to lower limb atherosclerosis in smokers and nonsmokers

Abstract: These findings indicate that risk factors for peripheral artery disease may differ between smokers and nonsmokers and further suggest that atherosclerosis in lower limb arteries is directly related to local hemodynamic forces among smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Systematic measurement of calf BP measurement has been reported for more than a century [1,4,5,17] but few studies have compared arm and calf BP measures [3][4][5][6][7]18]. In our report, supine calf SBP and DBP measures were in average 23 strengthening the validity of our findings [6,7].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Systematic measurement of calf BP measurement has been reported for more than a century [1,4,5,17] but few studies have compared arm and calf BP measures [3][4][5][6][7]18]. In our report, supine calf SBP and DBP measures were in average 23 strengthening the validity of our findings [6,7].…”
Section: Discussionsupporting
confidence: 71%
“…These data are in agreement with data reported in alternative populations [3] and suggest that such pro-atherogenic factors, which are acknowledged risk factors for peripheral artery disease [14], were associated with decreases in calf-arm DBP due to leg artery remodeling. In accordance with this assumption, previous studies showed that pro-atherogenic risk factors, such as smoking, are associated with higher prevalence of atherosclerotic plaques in popliteal arteries and decreased leg SBP, even in the absence of overt peripheral artery disease [18]. Conversely, it was noteworthy that age, a risk factor for peripheral artery disease [14], was associated with calf-arm DSBP in a direct rather than an inverse fashion.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…54,55 Even though lower extremity arterial disease and carotid artery disease to some extent share similar risk factors, 56 these two arterial territories are quite different in several aspects, such as prevalence of atherosclerosis 57 and regarding hemodynamic properties. 58 In conclusion, levels of biomarkers such as NT pro-BNP and MR-proADM can be used as independent predictors for clinically detected carotid artery stenosis during longterm follow-up of subjects from the general population.…”
Section: Characteristicmentioning
confidence: 89%